Smart Practice of Integrating Administrative Management and Human Resources of Chinese Local Governments under the Background of Digital Transformation (Lex localis - Journal of Local Self-Government, 2024)
Local Chinese governments face a challenge in improving the efficiency and quality of services provided during administrative management in the digital transformation era. The present study identifies three prime drivers for integration—technical, organisational efficiency, and policy support. Finally, it runs the hypotheses through the structural equation model for 133 data points from the questionnaire prepared for the local government administration. Superior integration is primarily contributed to by as discussed, technical support, organisational efficiency, and policy suit will improve effective management and organisational efficiency while reducing the cost and time required for integration; policy support will ensure legal compliance and standardisation. The study also finds that by adopting these factors, local governments can foster efficient and speedy integration of administrative management and human resources. These findings provide practical guidelines for the effective application of digital technology, organisational design, and public policies that promote innovation and sustainable development in public administration. It is necessary to investigate the particular technological approaches and multi-faceted methods for improving organisational performance in various digital contexts.